PENDIDIKAN BERBASIS TEKNOLOGI: PERMASALAHAN DAN TANTANGANNYA - Andri Asmara; Desta Lingga Sari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Educational Technology (TP) is designed to help solve educational problems, so as to be able to provide benefits in an effort to improve the quality of learning. Various forms of learning experiences, both those that can be achieved in the classroom and outside the classroom and learning messages, can be packaged by taking into account the principles and principles of educational technology. The use of learning technology is expected to be able to answer the challenges of technology-based education so that having educational messages can be packaged more systemically-systematically in physical and virtual packaging, which is no longer limited by the dimensions of space and time, so that students can receive it well, easily, and expanding, and creating a fun, flexible education in the dimensions of time, space, and developing the potential of students individually. Therefore, the rules and principles of educational technology, should be implemented into the whole process of education in subjects / subjects, self-development, and even become a school culture. In the framework of implementing the principles and principles of educational technology, of course there are still many problems that occur, including the implementation of learning processes in schools or learning in universities.